Timing of surgery for internal fixation of intracapsular hip fractures and complications at 1 year; a 32 year clinical study of 2, 366 patients at a single center. Issue 2 (February 2022) - Kanthasamy, S.; To, K.; Webb, J.I.; Elbashir, M.; Parker, M.J.
Highlights: Fixation of intracapsular fractures is a recognized option for both undisplaced and displaced fractures of the hip. Osteonecrosis and non-union are well recognized complications following, especially in displaced fractures. Balance between early appropriate care and physiological optimisation prior to hip fracture surgery is critical. Our study showed no relationship between time to surgery and development of osteonecrosis or non-union at 1 year. Female sex and displacement increased risk. Independent mobility and Targon® screw use were protective against non-union only. Abstract: Background: Timing of hip fracture surgery for the internal fixation of an intracapsular fracture remains controversial and few studies to date have been able to determine the optimum time to surgery in minimizing osteonecrosis and non-union with intracapsular fractures after fixation. Methods: Using a local hip fracture database managed by the senior author over a 32 year period, those who underwent osteosynthesis following intracapsular fractures were assessed for risk of development of non-union and osteonecrosis. Multivariate regression analysis was performed focusing on factors that were predictive of complications. Patient demographics, time from injury to surgery, fixation method, fracture pattern and complications at one year were reported. The primary outcome was whether delay to surgery contributed to risk of complications, defined as non-union or osteonecrosis. Secondary outcomes assessed the contribution of other factors to these complications. Results: 2, 366 patients were identified with an average age of 74.7 years and 66.5% were female. 1189 (50.3%) of fractures were displaced. 481 (20.3%) had a complication at one year following fixation. 78 (3.3%) were fixed by DHS, 6 (0.3%) by cephalomedullary nail, (1257) 53.1% by cannulated screws and 1025 (43.3%) by Targon® screw. Multivariate regression revealed no significant correlation between delay to surgery and complication rates (OR 0.99, 95% CI 0.99, 1.01, p = 0.55). Significant variables include female sex (OR 2.03, 95% CI 1.58, 2.62, p <0.0001), fracture displacement (OR 4.8, 95% CI 3.79, 6.14, p <0.0001), independent mobility (OR 0.64, 95% CI 0.47, 0.87, p = 0.004) and use of Targon® screws compared to parallel screws (OR 0.61, 95% CI 0.48, 0.76, p <0.0001). Conclusions: Our study demonstrates no relationship between timing of surgery for fixation of intracapsular fracture and complication rates. Female sex and fracture displacement increased risk of complications whereas independent mobility and use of Targon® screw device in comparison to parallel screws were protective against non-union but not avascular necrosis.